A Workshop of English Abstract Construction Scientific Writing of Diploma Students of Medical Record and Health Information of STIKes Mitra Husada Karanganyar - Erna Adita Kusumawati; Sri Sugiarsi (Indonesian Journal of Health Information Management Services, 2022)
ABSTRACT. One of the important aspects in scientific writing is abstract. Reseach abstract is constructed in two langugaes, i.e. Indonesian and English. However, most students has not been able to construct English abstract correctly according to English rules (tenses). This community service activity was aimed at improving students’ knowledge in constructing English abstract by applying correct tenses. The implementation of this community service was conducted through online workshop via Zoom platform. The activities were carried out by applying lecturing method, application, discussion, and exercise. The implementation of community service was successful because students’ understanding and knowledge in the tense usage in the abstract context improved significantly, that could be seen from the scores of pre-test and post-test. Keywords: technical gudance, tenses, English abstract